2018
DOI: 10.1002/dta.2466
|View full text |Cite
|
Sign up to set email alerts
|

Blood plasma level determination using an automated LC–MSn screening system and electronically stored calibrations exemplified for 22 drugs and two active metabolites often requested in emergency toxicology

Abstract: Fast and comprehensive qualitative and quantitative methods preferably by gas chromatography-mass spectrometry (GC-MS) and/or liquid chromatography-mass spectrometry (LC-MS) are needed to support the (differential) diagnosis of acute poisonings in emergency toxicology. One option is a commercially available qualitative screening solution based on LC-MS (Bruker Daltonik Toxtyper™, TT). Identified and toxicologically relevant compounds should be quantified to assess severity of poisonings. The aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…(18,23,29,(41)(42)(43) A study by Caspar et al, demonstrated its value in 24/7 toxicology by analysing 22 drugs and active metabolites in a qualitative and quantitative manner. (30) In the study done by Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner. (30,43) It would also avoid unnecessary treatment procedures in those that do not require them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(18,23,29,(41)(42)(43) A study by Caspar et al, demonstrated its value in 24/7 toxicology by analysing 22 drugs and active metabolites in a qualitative and quantitative manner. (30) In the study done by Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner. (30,43) It would also avoid unnecessary treatment procedures in those that do not require them.…”
Section: Discussionmentioning
confidence: 99%
“…(30) In the study done by Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner. (30,43) It would also avoid unnecessary treatment procedures in those that do not require them.…”
Section: Discussionmentioning
confidence: 99%
“…(18,23,29,(39)(40)(41) A study by Caspar et al demonstrated its value in 24/7 toxicology by analysing 22 drugs and active metabolites in a qualitative and quantitative manner. (30) In the study done be Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner. (30,41) It would also avoid unnecessary treatment procedures in those that do not require them.…”
Section: Discussionmentioning
confidence: 99%
“…(30) In the study done be Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner. (30,41) It would also avoid unnecessary treatment procedures in those that do not require them. The LC-MS/MS system may also be made more e cient using automation, this reduces the need for skilled personnel to run the equipment.…”
Section: Discussionmentioning
confidence: 99%
“…(18,19) (30) In the study done be Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner. (30,41) It would also avoid unnecessary treatment procedures in those that do not require them. The LC-MS/MS system may also be made more e cient using automation, this reduces the need for skilled personnel to run the equipment.…”
Section: Discussionmentioning
confidence: 99%